(untitled) (Journal of Society of Surgeons of Nepal, 2017)
Introduction: A functioning arteriovenous fistula (AVF) is essential for maintenance hemodialysis (HD) in a patient with chronic renal failure. This study explores the creation of AVF as an integral activity in a general surgical unit by a general surgeon. Methods: This is a hospital based cross sectional study done at Patan Hospital patients who underwent creation of AVF from January 2015 to June 2015 were included in the study. Patient demographic and clinical data were documented. Outcome and complications of AVF surgery were obtained over a 6 months period from the time of vascular access creation. Results: Thirty-seven patients were operated in the study period with a mean age of 35.44 years and M: F ratio of 2.7:1. There were 3 immediate and 3 delayed failure with 81.81% (n=27) patency rate at 6 months follow up. The maturation time was 3-7weeks (mean +/- SD of 4.83 +/- 1.053). Complication occurred in 4 patients, namely arm edema (n=3) and haematoma (n=1). Conclusion: The creation of AVF for HD performed in a general surgery unit is a safe procedure with satisfactory outcome and acceptable level of complications. Journal of Society of Surgeons of Nepal, 2015; 18 (2), Page: 2-5